TULUNGAGUNG PEOPLE'S VARIATIONS IN JAVANESE LANGUAGE IN WHATSAPP SOCIAL MEDIA: SOCIOLINGUISTIC STUDY - Purbosari, Riris (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
Javanese has variations in each region. As a district in East Java, Tulungagung has variations of the Javanese language. Javanese variations are also used in communication on WhatsApp. This research aims to explain the variations of Javanese language used by Tulungagung people in communicating on WhatsApp. The theoretical basis used is sociolinguistics. This research uses descriptive qualitative research methods. The source of research data is the people of Tulungagung who communicate on WhatsApp. Research data consists of written and verbal data from the researcher's personal WhatsApp. The method of providing data used is listening and speaking. Based on research, the Javanese language variations used are the use of slang by young men and women, greetings by young and adult men and women, Tulungagungan dialect by men and young and adult women, and krama desa variation by young and adult men and women. Language variations reflect the socio-cultural identity of society. The use of language variations has a social function, namely the function of familiarity, politeness, and indicating identity. Keywords: Language variation, Sociolinguistics, Socio-Cultural Identity, Tulungagung Community